Transmission of Citrus leprosis virus C by Brevipalpus phoenicis (Geijskes) to Alternative Host Plants Found in Citrus Orchards - Nunes, M. A.; Oliveira, C. A. L. de [UNESP]; Oliveira, M. L. de [UNESP]; Kitajima, E. W.; Hilf, M. E.; Gottwald, T. R.; Freitas-Astua, J. (Amer Phytopathological Soc, 2012)
The equivalent of US$75 million is spent each year in Brazil to control Brevipalpus phoenicis, a mite vector of Citrus leprosis virus C (CiLV-C). In this study, we investigated the possibility that hedgerows and windbreaks normally found in citrus orchards could host CiLV-C. Mites confined by an adhesive barrier were reared on sweet orange fruit with leprosis symptoms then were transferred to leaves of Hibiscus rosa-sinensis, Malvaviscus arboreus, Grevilea robusta, Bixa orellana, and Citrus sinensis. Ninety days post infestation, the descendant mites were transferred to Pera sweet orange plants to verify the transmissibility of the virus back to citrus. Nonviruliferous mites which had no feeding access to diseased tissue were used as controls. Local chlorotic or necrotic spots and ringspots, symptoms of leprosis disease, appeared in most plants tested. Results generated by reverse-transcription polymerase chain reaction with primers specific for CiLV-C and by electron microscope analyses confirmed the susceptibility of these plants to CiLV-C.